Dendrimer conjugates for light-activated delivery of antisense oligonucleotides1. Issue 44 (16th May 2015) - Yuan, Ahu; Hu, Yiqiao; Ming, Xin
<x xml:space="preserve">Abstract</x> PAMAM dendrimer conjugates are used to co-deliver oligonucleotides and photosensitizers to cancer cells. After photo-irradiation, substantial reporter eGFP expression is produced by functional delivery of a model oligonucleotide.